Greenhouse farming as adaptation to climate change in Nigeria (2011)
The effect of climate change in recent times has disrupted the onset and duration of seasons in Nigeria manifesting in the reduction of both staple and cash crops, and livestock yields. This has transformed the country to a major importer of those agricultural produce she hitherto exported. As a country where over 70% of the population depends on agriculture for survival, the impacts of climate change are a major threat to both food security and the general economy. Remedial measures which have been suggested including adoption of agronomic and tested practices, reduced burning and afforestation. An option that could be of great potential in ameliorating this situation but which has not been practiced especially in the production of specialty crops is the use of greenhouse farming. This paper discusses the impact of climate change on Nigerian agriculture. The potentials and logistics are required for effective use of greenhouse farming as an adaptation to climate change in Nigeria. It is suggested that research should be carried out to select appropriate glazing materials. The provisions of training and credit facilities for interested farmers are recommended for effective utilization of the system.